Consensus statement - Sexual violence in sport: American Medical Society for Sports Medicine position statement - Scott Koontz, J.; Mountjoy, M.; Abbott, K. E.; Miller Aron, C.; Basile, K. C.; Carlson, C. T.; Chang, C. J.; Diamond, A. B.; Dugan, S. A.; Hainline, B.; Herring, S.; Hopkins, B. E.; et al. (British Journal of Sports Medicine, 2021)
The American Medical Society for Sports Medicine (AMSSM) convened a group of experts to develop a Position Statement addressing the problem of sexual violence in sport. The AMSSM Sexual Violence in Sport Task Force held a series of meetings over 7 months, beginning in July 2019. Following a literature review, the Task Force used an iterative process and expert consensus to finalise the Position Statement. The objective of this Position Statement is to raise awareness of this critical issue among sports medicine physicians and to declare a commitment to engage in collaborative, multidisciplinary solutions to reduce sexual violence in sport.